2013
DOI: 10.3810/pgm.2013.07.2686
|View full text |Cite
|
Sign up to set email alerts
|

A Canadian Study of the Cost-Effectiveness of Apixaban Compared With Enoxaparin for Post-Surgical Venous Thromboembolism Prevention

Abstract: : This is the first economic evaluation of apixaban use for VTE thromboprophylaxis in the Canadian setting, and our study results show apixaban to be a cost-effective treatment alternative to preventive treatment with enoxaparin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 30 publications
0
11
0
3
Order By: Relevance
“…A cost analysis using the ADVANCE studies indicated improved cost-effectiveness with the use of apixaban compared with enoxaparin. 44 In line with these findings, a comparison of all Factor Xa inhibitors with the 2 LMWH agents (enoxaparin and dalteparin) found the Factor Xa inhibitors to be the economically superior option. 45 Fondaparinux.…”
Section: Novel Factor Xa Inhibitorsmentioning
confidence: 75%
“…A cost analysis using the ADVANCE studies indicated improved cost-effectiveness with the use of apixaban compared with enoxaparin. 44 In line with these findings, a comparison of all Factor Xa inhibitors with the 2 LMWH agents (enoxaparin and dalteparin) found the Factor Xa inhibitors to be the economically superior option. 45 Fondaparinux.…”
Section: Novel Factor Xa Inhibitorsmentioning
confidence: 75%
“…Apixaban is currently FDA-approved to reduce the risk of stroke and systemic embolism in patients with nonvalvular atrial fibrillation, for the prophylaxis of DVT, which may lead to PE, in patients who have undergone TKR or THR, for the treatment of DVT and PE, and for the reduction in the risk of recurrent DVT and PE following initial therapy. The predictable pharmacokinetics, limited medication interactions, lack of required laboratory monitoring, and potentially improved cost-effectiveness 48 render apixaban an attractive alternative to other anticoagulants such as warfarin. However, long-term safety data is not yet available, and RCT data is lacking in special populations.…”
Section: Discussionmentioning
confidence: 99%
“…20 Por outro lado, Revankar et al, em uma avaliação econômica do uso de apixabana, mostrou que essa droga é uma opção benéfica para a prevenção de TVP pós-cirúrgico, em comparação com a enoxaparina. 21 A edoxabana é um inibidor direto oral do fator Xa. O estudo STAR E-3 comparou 30 mg de edoxabana uma vez ao dia, com início seis a 24 horas após a cirurgia, ou enoxaparina 20 mg, subcutâneo, duas vezes ao dia, começa 24 a 36 horas após a cirurgia por 11 a 14 dias depois de ATJ, em pacientes no Japão e Taiwan.…”
Section: Métodos Farmacológicosunclassified